Induction of peptide-specific primary cytotoxic T lymphocyte responses from human peripheral blood. - Plebanski, M; Allsopp, C; Aidoo, M; Reyburn, H; Hill, A (1995)
Various protocols were developed and compared for eliciting specific cytotoxic T lymphocyte (CTL) cell lines from the unselected human peripheral blood mononuclear cells of naive donors. Interleukin-7 and CD4+ T cells primed in vitro by keyhole limpet hemocyanin were shown to act together in the generation of these responses. Primary responses were consistently induced with a variety of different HLA class I-binding malarial peptides. Primary CTL responses could be induced from unselected CD8+ and from CD45RA+CD8+ T cells. The CTL lines derived from these naive donors were CD8+ and demonstrated a high level of HLA class I-restricted killing for > 3 months after priming in vitro. They were also able to recognize and kill targets infected with a recombinant vaccinia virus containing the full-length antigen. In addition, this same protocol enhanced up to fourfold the levels of secondary CTL responses induced. The optimal method presented for naive cytotoxic T cell stimulation is simple, rapid and generally applicable and should provide a useful tool for both basic research and human therapy.